TALAQIY AL-TAGHRIDAH AL-SYI’RIYAH HISAB AL-SYA’IR MOHAMMED ALMOQREN ANMUDZAJAN - Zafer Moshbbab Mohammad Alkinani (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2017)
This contemporary age faced large technical revolutions which have huge effects on all life areas. These technical revolutions cause dramatic changes in human natures particularly in terms of consumptions and communication. Therefore, the literature and its branches could not be separated from these technical age influences as the literature interacted with these evolutionary products and employed this age resources. Therefore, the focus of this study was the perception of poetical tweets on a Twitter account belonged to a poet namely Mohammed Almoqren. The steps of this study covered interjection, rerouting, written interaction, contradiction, visual shaping, dynamic shaping, summary and conclusion.